An evaluation of a remote training system with bodily reliving experience for windsurfing - Goto, M.; Esaki, K.; Inoue, T.; Seshimo, H.; Hirano, T. (Sports Engineering, 2025)
Windsurfing is a sport that involves sailing far from the coast. Traditionally, coaches observe windsurfers` sailing from the shore or through video recordings. They provide feedback on observed weaknesses once back on land. The windsurfers then attempt to correct those weaknesses during their next training session at sea. However, it is difficult for windsurfers, especially professionals whose required corrections are minor, to accurately reflect such feedback from coaches in future wave and wind conditions. In this study, we have developed a training system called the Bodily Sensory Reproduction Player that senses the movements of windsurfing equipment at sea and reproduces the same movements on the basis of the collected data. This paper proposes a new training method for windsurfing that enables windsurfers to relive their movements over and over again under the same conditions using the proposed system. This paper also reports the results of two case studies conducted using the proposed system with actual windsurfers and coaches. The results demonstrated the feasibility of a new training method using the proposed system.